Implementation of L3 Function on Virtualization Environment using Virtual Machine Approach - Marcel Yap (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
There are 2 approaches to implement layer 3 network function on virtualization platforms, the first approach uses the conventional physical devices; while the second is software-based. Several previous studies have been carried out to test the performance of L3 function on virtualization using software-based and obtained positive result for the performance over the physical-based. While the previous studies were limited only within the scope of testing environment, this paper tries to extend the study not only limited to the performance test based-on RFC 2544 standard, but also implementation in the production environment using virtual machine (VM) approach. Mikrotik CHR (Cloud Hosted Router) designed specifically for virtualization environment will be used as the L3 platform on the VM. Implementation in the production environment was conducted at University computer laboratory that has 207 desktops (190 in the form of virtual desktops, 17 in the form of PCs) not including user' devices that connected via WiFi networks. VM-based approach for routing functions (Layer 3) using Mikrotik CHR has proven to be stable and sufficient for use in the computer laboratory after 6 months of usage. Performance test also shown that VM-based L3 function had higher transfer rates; physical-based router was about 23,4% slower for 1 routing load and 4,25% slower for 2 routings load. The characteristic of VM itself also add some benefits like VM snapshot and migration for recovery. The test also revealed that VM-based L3 function prone to performance penalties when more than one routing load performed compared with physical-based.